(untitled) (Research, Society and Development, 2022)
The aim of the study was to perform a morphological analysis of the effects of osteoporosis on the periodontal ligament of rats with periradicular injury. Adult rats (n = 24), of the Wistar lineage, 3 months old, were included in the study. Twelve animals were ovariectomized (group OVX) and 12 were operated by simulation (group C). One hundred and twenty days after surgery, all animals were anesthetized, and in each animal, periradicular lesion was developed in the mandibular left first molar, by making a coronal opening in the mesial fossa on the occlusal surface until the pulp was exposed. At the end of each experimental time interval (21 and 40 days after the lesion developed), the animals were sacrificed, and blood was collected to confirm the effects of castration by serum estrogen measurement. The jaws were removed and prepared for quantitative analysis of the periodontal ligament thickness, by using an optical microscope. Comparative analysis of the data was performed using the non-parametric Kruskal-Wallis and Dunn Multiple Comparison tests. A reduction in serum estrogen levels was observed in the OVX groups (p <0.01), and a significant increase in the periodontal ligament thickness in Group C 21, when compared with Group OVX 40 days (p <0.01), and Group C 40 compared with Group OVX 40 days (p<0.01). In all samples with osteoporosis, there were signs of resorption in the alveolar bone, and significant periodontal ligament thickening in animals with longer exposure to the disease.